Conformance Testing with Abstract State Machines - Grieskamp, Wolfgang; Gurevich, Yuri; Schulte, Wolfram; Veanes, Margus (EUROCAST 2001, 2001)
One benefit of executable specifications is that they allow one to test the conformance of implementations to their specifications. We illustrate this on the example of Universal Plug and Play devices. The necessary test sequences are generated automatically from ASM specifications.